Star wars, episode IV, A new hope [videorecording (DVD)] - Ford, Harrison, 1942-; Fisher, Carrie; Hamill, Mark; Lucas, George, 1944- (Star wars trilogy., 2004)
Princess Leia is captured and held hostage by the evil Imperial forces in their effort to take over the galactic Empire. Luke Skywalker, Han Solo, and two robots (R2-D2 and C-3PO) work together to rescue the princess and restore justice in the Empire.